Assigning the Absolute Configurations of Chiral Primary Amines Based on Experimental and DFT-Calculated 19F Nuclear Magnetic Resonance - Yang, Shiwei; Bian, Guangling; Sa, Rongjian; Song, Ling (Frontiers in Chemistry, 2019)
In this work, a novel method for assigning the absolute configuration of a chiral primary amine has been developed based on the experimental and DFT calculated 19F NMR chemical shift differences of its derived two fluorinated amides by reacting with two enantiomers of a chiral derivatizing agent FPP (α-fluorinated phenylacetic phenylselenoester) separately. Comparing the experimental chemical shift difference Δδα-FR,S of (R)-FPA-amide/(S)-FPA-amide with the calculated Δδα-FR,S of (R)-FPA-(R)-amide/(S)-FPA-(R)-amide, if the experimental Δδα-FR,S has the same symbol (positive or negative) as one of the theoretical Δδα-FR,S, the assigned configuration of the amine is considered to be consistent with the theoretical one. Our method could be applied to a broad substrate scope avoiding wrong conclusion due to empirical judgment.